2007
DOI: 10.1002/cb.211
|View full text |Cite
|
Sign up to set email alerts
|

Deterring illegal downloading: the effects of threat appeals, past behavior, subjective norms, and attributions of harm

Abstract: The study employs two experiments to examine the effectiveness of various strategies used to dissuade consumers from downloading music illegally. The research investigates two specific strategies that the recording industry has used: (1) fear or threat appeals (e.g., the threat of punishment, such as fines and/or jail time), and (2) attribution of harm (informing consumers of the harm caused by the illegal downloading of music, such as financial loss to either the artist or the recording company). The study al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 10 publications
2
65
0
Order By: Relevance
“…Knopper (2007) reported that there had only been 18,000 lawsuits targeting downloading between Sep 2003 and 2006 and it follows that an increase in the incidence of penalties would increase the public's perception of the risk of consequences. The need to increase perceptions of the probability of prosecution aligns with the findings of past research (Levin et al 2007;Peace et al 2003) and is consistent with Witte's Extended Parallel Process Model (Witte 1992), which recognizes that individuals need to perceive that they are susceptible to a threat to be motivated to take action (Witte and Allen 2000). It is worth mentioning here that media coverage is only one form of deterrence and we did not consider other preventative methods.…”
Section: Contributionsupporting
confidence: 71%
See 1 more Smart Citation
“…Knopper (2007) reported that there had only been 18,000 lawsuits targeting downloading between Sep 2003 and 2006 and it follows that an increase in the incidence of penalties would increase the public's perception of the risk of consequences. The need to increase perceptions of the probability of prosecution aligns with the findings of past research (Levin et al 2007;Peace et al 2003) and is consistent with Witte's Extended Parallel Process Model (Witte 1992), which recognizes that individuals need to perceive that they are susceptible to a threat to be motivated to take action (Witte and Allen 2000). It is worth mentioning here that media coverage is only one form of deterrence and we did not consider other preventative methods.…”
Section: Contributionsupporting
confidence: 71%
“…Individuals perceive that digital piracy has a low risk of prosecution (Al-Rafee and Cronan 2006; Cheng et al 1997), a factor found to predict intention to pirate (Ang et al 2001;Coyle et al 2009;Liao et al 2010;Peace et al 2003). Furthermore, increasing awareness of the risk of prosecution leads to less favorable attitudes toward downloading (Chiou et al 2005), and decreases intention to pirate (Glass and Wood 1996), although the threat may have to be severe (Levin et al 2007). The relationship also differs for men and women; women are more likely to be influenced by perceived risk of consequences than men (Chiang and Assane 2008).…”
Section: Digital Piracymentioning
confidence: 97%
“…Other scholars have measured habit strength by employing past piracy behavior (PPB) as a proxy (Robertson et al 2011;Levin et al 2007;Cronan and Al-Rafee 2007;Coyle et al 2009;Lysonski and Durvasula 2008;Higgins et al 2005), finding a significant positive relationship between PPB and either intention to pirate or actual pirating behavior. Although the two are closely related, we fail to recognize a direct connection between PPB and habit.…”
Section: Habitual Patterns In Digital Piracymentioning
confidence: 97%
“…In this vein, researchers tend to associate illegal downloading with physical theft, arguing that it can be explained by the same motivators that drive traditional shoplifting (Shanahan and Hyman 2010), and relate the willingness to pirate to the willingness to endorse in other morally questionable acts (Levin et al 2004). Consequently, a common underlying assumption is that illegal downloaders possess less developed ethical standards (Robertson et al 2011;Chaudhry et al 2011;Gopal et al 2004;Levin et al 2004Levin et al , 2007Thong and Chee-Sing 1998;Gopal and Sanders 1997;Lysonski and Durvasula 2008;Cronan and Al-Rafee 2007;Tan 2002). Jambon and Smetana (2012) dispute the operationalization of ethical propensity as a general trait that determines how individuals arrive at the evaluation of ethical issues.…”
Section: Ethical Perspectivementioning
confidence: 98%
“…The ideology of freeware, beliefs regarding consumer rights, expectations of reciprocity, and antipiracy norms can sway attitudes towards piracy 33 . Some individuals do not recognize a moral imperative because attributions of harm to artists or record labels do not resonate 34 . In fact, some believe that the music industry has taken advantage of consumers by charging high prices, forcing them to purchase entire CDs instead of individual tracks, producing low quality products, and keeping an unfair portion of the profits 35,36,37,38 .…”
Section: Moral and Ethical Perspectivementioning
confidence: 99%